PROGNOSTIC VALUE OF INTSTRUMENTAL DIAGNOSTICS IN CHRONIC CORONARY HEART DISEASE. DATA FROM “PROGNOS CHD” - S. N. Tolpygina; S. Yu. Martsevich; E. A. Gofman; A. D. Deev (Кардиоваскулярная терапия и профилактика)
Aim. To study the role of instrumental findings in the evaluation of long-term outcomes and life for stable coronary heart disease patients (CHD) in the “PROGNOS CHD” registry.Material and methods. In the frame of registry the retro-, prospective, observational, cohort study is performed, that included all patients inhabitants of Moscow region, consequently admitted to the hospital of SSRCPM from 01.01.2004 to 31.12.2007 planned with the admittance dignosis “CHD”, and for whom the coronary arteriography was done. Totally 641 pt (500 male, 141 female). Mean follow-up period 3,9 years (0,76–6,52). At the end the life status defined for 551 (86%) patient. Into analysis the data from instrumental methods included: ECG, echocardiography (Echo), exercise testing (ET).Results. The risk for primary endpoint (PEP) was increased by: scar changes in resting ECG — 2,2 times (p=0,0007), tachicardia 2,7 times (p=0,02), rhythm disorders 1,76 times (p=0,04); valve stenoses by Echo — 3 times (p=0,04), ventricle dilation 1,8 times (p=0,02), local contractility defects 1,8 times (p<0,003); ST horizontal depression during ET — 2,2 times (p=0,04, ns by crosstabulation). Risk of PEP decreased by the ET possibility to perform — by 1,6 times (p=0,049), normal EF by 1,5 times (p=0,001). The prevalence of secondary endpoint was increased by: scar changes on ECG — 1,5 times (p=0,01); positive ET — 13,2 times (p=0,01), downsloping ST depression at ET — 2,1 times (p=0,01), low and medium exercise tolerance — 2,8 (p=0,04) and 2,1 times (p=0,04), resp. The worse for PEP were scar changes on ECG, dilation of the heart chambers, disordered local contractility of LV, valve stenoses by Echo, and positively influenced outcomes — normal EF and the fact of ET performing.Conclusion. High predictive significance of various broad known instrumental methods of diagnostics, like resting ECG, Echo or ET, make possible to use them for risk stratification of cardiovascular complications development in chronic CHD and for defining of indications to invasive diagnostic procedures.